Preparation and Inverstigation of MEH-PPV Films Used for White Light Emitting Diodes - Dinh, Nguyen Nang; Chung, Do Ngoc; Nam, Nguyen Phuong Hoai; Duong, Pham Hong (Communications in Physics, 2011)
With the aim to prepare white Light Emitting Diode (WLED), the conjugate polymer films like (Poly[2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) were investigated. Spectroscopic (absorption and emission) spectra of the MEH-PPV films showed that this polymer is suitable for casting onto the chips of the blue InGaN LED to make WLED. The luminous flux measured on the WLEDs in the integrating sphere proved that the white light emission can be obtained from the combination of inorganic LED and conjugate (MEH-PPV) polymers with an optimal thickness and a high quality. The aging process of MEH-PPV films was found to be strongly dependent post-treatment conditions. Reasonable heat treatment condition for the MEH-PPV polymers was suggested as in vacuum of 5×10-2 Pa at a temperature of 120°C in, for 2 hous.